2019
DOI: 10.1016/j.tws.2019.03.019
|View full text |Cite
|
Sign up to set email alerts
|

Analytical behavior of concrete-filled aluminum tubular stub columns under axial compression

Abstract: This paper presents numerical investigation of circular concrete-filled aluminum tubular (CFAT) stub columns under axial compression. The numerical models were developed using the finite element (FE) package ABAQUS. The parameters commonly employed in conventional CFST FE modeling have been discussed in this study. The nonlinearities of concrete and aluminum materials and the interaction between concrete and aluminum tube were considered. Numerical models were validated against collected experimental data. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(23 citation statements)
references
References 23 publications
0
18
0
Order By: Relevance
“…At the end of this stage, the axial pressure of circular CFAT was 1.5 times that of square CFAT. It is indicated that the average slope of the curve at this stage can indirectly represent the ductility of CFAT, which is similarly described by ductility index (DI) in Zhao and Han's study [8]. The smaller the slope is, the worse the ductility is.…”
Section: Analysis Of Load-deformation Historiesmentioning
confidence: 88%
See 1 more Smart Citation
“…At the end of this stage, the axial pressure of circular CFAT was 1.5 times that of square CFAT. It is indicated that the average slope of the curve at this stage can indirectly represent the ductility of CFAT, which is similarly described by ductility index (DI) in Zhao and Han's study [8]. The smaller the slope is, the worse the ductility is.…”
Section: Analysis Of Load-deformation Historiesmentioning
confidence: 88%
“…Gardner and Ashraf [7] first put forward the non-linear material model of aluminum alloy materials. On this basis, Wang et al [8] studied the bearing capacity and stiffness of circular aluminum tube concrete column under axial compression through experiments and numerical simulations. It was concluded that circular CFAT specimen had good bearing capacity and ductility as conventional CFST specimen.…”
Section: Introductionmentioning
confidence: 99%
“…In a more recent study, Zhou & Young [137] assessed experimentally the compressive response of concrete-filled double-skin tubes and suggested formulae for their ultimate capacity. Wang et al [138] used the data reported by Zhou & Young [135] and evaluated whether the "nominal yield strength" method adopted by GB 50936 [139] for CFST is applicable to CFAT, concluding that it provides conservative but reliable predictions.…”
Section: Web Cripplingmentioning
confidence: 99%
“…Concrete-filled steel tube (CFST) composite columns have been widely used in various building structures for their high bearing capacity, excellent plasticity and seismic performance (Wang et al, 2019;Ji et al, 2021a;Ji et al, 2021b). With the development of concrete materials (Cai et al, 2021;Ji et al, 2021c;Ding et al, 2021), high-performance concrete (HPC) (Yoo et al, 2012) has been commonly used in engineering for its selfcompactness, high strength, high permeability and long service life (Huang et al, 2009;Sung et al, 2012;Wang and Liang, 2012;Yoon and Jang, 2015).…”
Section: Introductionmentioning
confidence: 99%